Expanding and Contracting Definitions of Syncopation: Commentary on Temperley 2019 - Condit-Schultz, Nat (Empirical Musicology Review, 2019)
In the article Second-Position Syncopation in European and American Vocal Music, David Temperley presents an empirical, socio-cultural survey of syncopation in 19th-century Western music. He espouses the following novel ideas about operational definitions of syncopation: 1) that syncopations on the second position of a duple hierarchy are musically, and culturally, distinct from fourth-position syncopations; 2) that more detailed operational definitions of syncopation, what Temperley calls "acute" syncopations, are needed to properly understand syncopation. Following up on Temperley's work, I apply his definitions of syncopation to a corpus of more recent Anglo-American popular music (Gauvin, Condit-Schultz, & Arthur 2017). I discuss how Temperley's definitions must be adapted and expanded to fit this different, more diverse, dataset, proposing several new syncopation definitions of my own. I also discuss some statistical assumptions that ought to be better addressed in future work, and speculate on how inconsistencies of music notation might hinder historical studies like Temperley's.